2019
DOI: 10.1590/0004-282x20190180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oropharyngeal dysphagia in hereditary spastic paraplegias

Abstract: Hereditary spastic paraplegias (HSP) are a group of genetic diseases characterized by lower limb spasticity with or without additional neurological features. Swallowing dysfunction is poorly studied in HSP and its presence can lead to significant respiratory and nutritional complications. Objectives: The aim of this study was to evaluate the frequency and clinical characteristics of dysphagia in different types of HSP. Methods: A two-center cross-sectional prevalence study was performed. Genetically confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A few studies previously reported some of these symptoms in patients with SPG7 mutations. 6,[62][63][64][65] Optic atrophy and dopa-responsive parkinsonism were also reported in a patient with concurrent AFG3L2 and SPG7 heterozygous variants. 42 Similar to other genes involved in HSP, SPG7 may be involved in a continuum of spastic neurogenetic disorders, and SPG7 variants should not be ruled out only because of the presence of rare clinical manifestations.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A few studies previously reported some of these symptoms in patients with SPG7 mutations. 6,[62][63][64][65] Optic atrophy and dopa-responsive parkinsonism were also reported in a patient with concurrent AFG3L2 and SPG7 heterozygous variants. 42 Similar to other genes involved in HSP, SPG7 may be involved in a continuum of spastic neurogenetic disorders, and SPG7 variants should not be ruled out only because of the presence of rare clinical manifestations.…”
Section: Discussionmentioning
confidence: 77%
“…We also report several rare clinical features of SPG7, including dopa‐responsive parkinsonism, dysphagia, dysmetria, jaw jerk, ptosis, ophthalmoplegia, optic atrophy, and hands dystonia in biallelic SPG7 patients. A few studies previously reported some of these symptoms in patients with SPG7 mutations 6,62‐65 . Optic atrophy and dopa‐responsive parkinsonism were also reported in a patient with concurrent AFG3L2 and SPG7 heterozygous variants 42 .…”
Section: Discussionmentioning
confidence: 82%
“…In this study we also report several rare clinical features of SPG7, including dopa-responsive parkinsonism, dysphagia, dysmetria, jaw jerk, ptosis, ophthalmoplegia, optic atrophy and hands dystonia in bi-allelic SPG7 patients. A few studies previously reported some of these symptoms in patients with SPG7 mutations (Van Gassen et al , 2012; Pfeffer et al , 2014; Pedroso et al , 2018; De la Casa-Fages et al , 2019; Jacinto-Scudeiro et al , 2019). Optic atrophy and dopa-responsive parkinsonism were also reported in a patient with concurrent AFG3L2 and SPG7 heterozygous variants (Magri et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Arquivos de Neuropsiquiatria, Jacinto-Scudeiro et al 4 analyzed affected individuals with pure and complicated forms of HSP and they detected that clinically significant oropharyngeal dysphagia was only present in complicated forms of the disease. Specifically, SPG11 and CTX presented highest risks for dysphagia, indicating that surveillance of swallowing function should be part of the management of patients with these disorders.…”
mentioning
confidence: 99%